Uncovering the Relationships Among Entrepreneurial Competency Variables in University Students: A CFA Approach - Hayati, Nur; Susilo, Herawati; Ibrohim, Ibrohim; Balqis, Balqis (Corolla International Conference, 2025)
Entrepreneurship has a crucial role in creating jobs and triggering economic development. Furthermore, entrepreneurship offers a solution to social problems and the oversupply of university graduates. Therefore, entrepreneurship is essential for students, including science students. This study seeks to uncover the relationships among the variables of entrepreneurial competencies, consisting of knowledge, skills, and attitudes. The study design was a cross-sectional survey conducted from January to March 2023. The sampling technique was carried out by purposive sampling involving 346 science undergraduate students as research samples. The instrument used in this study was a questionnaire consisting of 15 statements of knowledge competency aspects, 16 statements of skill competency aspects, and 21 statements of entrepreneurial attitude competency aspects. This study employed Confirmatory Factor Analysis as the data analysis technique, conducted using AMOS software. The analysis results demonstrated that there was a very close and positive correlation in each variable of entrepreneurial competency. Knowledge competency was found to be positively related to skill competency (correlation coefficient of 0.817), knowledge competency was positively correlated with attitude competency (correlation coefficient of 0.870), and skill competency was positively correlated with attitude competency (correlation coefficient of 0.955). Each indicator provided a varying contribution in explaining aspects of entrepreneurial competency as indicated by the coefficient of determination (R2).